Identitas Nasional di Kalangan Remaja - Gusnita Gusnita; Mita Sari; Sasmi Nelwati (Universitas 45 Surabaya, 2024)
National Identity is a national identity which is the characteristics or characteristics, feelings or beliefs, culture or habits of a nation that distinguishes one nation from another. Indonesia's national identity is pluralistic which consists of a fundamental identity, namely Pancasila, instrumental identity, namely the 1945 Constitution. The digital era has brought many positive changes that we can now utilize as much as possible. But at the same time, the digital era also brings many negative impacts, causing new challenges in human life in this digital era. Thus, these efforts can ensure the maintenance of the nation's identity and integrity. By fostering the spirit of nationalism and patriotism, a natural sense of love for the country will grow, which is one form of effort to maintain the identity and integrity of the nation.